Assessment of the Performance of Medical Records in Outpatient Registration at the Maternal and Child Special Hospital "Pertiwi" Makassar - Muhammad Thabran Talib; Evi Lusiana; Ahmad Jayadie (Aloha International Journal of Health Advancement (AIJHA), 2022)
To achieve the goal of good medical record services, it is necessary to improve the quality of medical records by the Medical Record Work Unit, where these quality improvement efforts are highly dependent on the availability of clear, accurate, reliable data and information, and timely presentation. The health data and information contained in the medical record file is very useful for the management of health care institutions to assess the services provided, whether they are of good quality, efficient and effective. This study aims to determine: 1) the performance of medical records and health information services; 2) clarity of information about service flow; 3) speed of service at registration; and 4) patient satisfaction in the outpatient unit registration department, at Maternal and Child Special Hospital "Pertiwi" Makassar. This type of research is quantitative with a descriptive approach. The study was conducted from January to February 2022, involving 135 patients as respondents. Data was collected by filling out a questionnaire with a Likert scale. Furthermore, descriptive data analysis was carried out. The results of the analysis show that the distribution of clarity of information was: very good = 1,452, good = 726, poor = 90, very poor = 25, with a value of 84.92%. The distribution of service speed was: very good = 1,552, good = 669, poor = 86, very poor = 21, with a value of 86.22%. The distribution of patient satisfaction was: very good = 1,600, good = 693, poor = 50, very poor = 19, with a value of 87.48%. Furthermore, it was concluded that the medical record service in the outpatient registration section was very good, both in terms of clarity of information, speed of service and patient satisfaction. Keywords: medical record; patient registration; outpatient unit; clarity; speed; patient satisfaction